Splanchnic and renal elimination and release of catecholamines in cirrhosis. Evidence of enhanced sympathetic nervous activity in patients with decompensated cirrhosis. Issue 10 (October 1984) - Henriksen, J H; Ring-Larsen, H; Kanstrup, I L; Christensen, N J
Abstract : Plasma noradrenaline (NA) and adrenaline (A) concentrations were determined in different vascular areas in 32 patients with cirrhosis and in nine controls during a right sided heart, liver, and renal vein catheterisation. The patients were divided into four groups: (I) Compensated (without ascites); (II) Recompensated on diuretic treatment because of former ascites; (III) Decompensated (with ascites) without treatment and (IV) Decompensated on diuretic treatment. Median arterial noradrenaline concentrations were 1.48, 1.07, 2.66, 4.14 and 2.50 nmol/l in controls, group I, II, III, and IV, respectively, the three last mentioned values being significantly raised (p less than 0.01). Median arterial adrenaline concentrations were not significantly increased. In patients arterial-hepatic venous extraction ratios of noradrenaline and adrenaline were on the average 25% (p less than 0.01) and 20% (p less than 0.02) less than those of the controls, indicating a slightly reduced splanchnic elimination of catecholamines in cirrhoses. In controls and group I significant renal venous-arterial noradrenaline differences were absent (0.00 and 0.03 nmol/l) while renal venous-arterial noradrenaline differences were significantly increased in groups II, III and IV (0.47, 0.53 and 0.68 nmol/l, p less than 0.01), indicating a significant net release of noradrenaline from the kidneys in recompensated and decompensated patients. Renal extraction of adrenaline was normal. In conclusion, increased arterial noradrenaline in decompensated and recompensated cirrhosis is only to a limited extent owing to reduced net splanchnic elimination. More likely the increase is caused by release of noradrenaline from the kidneys and possibly other organs indicating enhanced sympathetic nervous tone in these conditions.